Association between the hemoglobin-to-red cell distribution width ratio and three-month unfavorable outcome in older acute ischemic stroke patients: a prospective study - Huang, Luwen; Li, Linlin; Ouyang, Qing-rong; Chen, Ping; Yu, Ming; Xu, Lei (Frontiers in Neurology, 2025)
ObjectiveAcute ischemic stroke (AIS) is a prevalent acute condition among older individuals. This study is the first investigation of the link between the HRR and unfavorable three-month outcome in older AIS patients.MethodsThis secondary research used data from a sample of 1,470 older AIS patients collected from a South Korean hospital between January 2010 and December 2016. Multiple imputation was applied to account for absent values. Binary logistic regression analysis was used to examine the relationship between the baseline HRR and adverse outcome at three-month. Restricted cubic spline analysis was employed to evaluate the correlation between HRR levels and adverse outcome. Interaction tests were performed to discern variations among subgroups.ResultsAt 3 months, the overall incidence of adverse events was 31.43%, with a median HRR of 9.49. Compared to those with a lower HRR (Q1), the adjusted odds ratios (ORs) for the HRR in Q2, Q3, and Q4 were 0.61 (95% CI: 0.41–0.92, p = 0.017), 0.49 (95% CI: 0.31–0.78, p = 0.003), and 0.54 (95% CI: 0.31–0.92, p = 0.025), respectively. The correlation between the HRR and adverse outcome was non-linear (p < 0.05). An inflection point threshold of 10.70 was established via RCS analysis. Each 1-unit increase in HRR on the left side of the infection point was associated with a 24.0% decrease in the likelihood of adverse outcomes (OR = 0.76, 95% CI: 0.66–0.86, p < 0.001). ROC analysis revealed that HRR had the highest AUC (0.64, 95% CI: 0.61–0.67), followed by hs-CRP (0.60, 95% CI: 0.57–0.63), FPG/HbA1c (0.59, 95% CI: 0.55–0.63), and WBC (0.55, 95% CI: 0.51–0.58).ConclusionA lower HRR was correlated with a higher risk for adverse outcome in older AIS patients.